Quitosana no desenvolvimento de novos produtos alimentícios e biotecnológicos - Sousa, Felipe Sanderson Ribeiro de (Universidade Federal Rural do Semi-Árido, 2019)
Chitosan is a biomaterial that has properties such as biodegradability, inability to cause toxic effects, and preservative property in food, since it inhibits and eliminates a broad spectrum of bacteria, including bacteria of great interest in meat products, besides acting as an additive. It is intended to use chitosan to produce a new formulation of sausage meat of agouti, and to develop a biomembrane composed of chitosan and propolis of the bee Frieseomelitta doederleini. For better understanding, the research was separated into chapters. In the first chapter, the sausage was made with kumquat meat, in which it was milled and weighed in proportions, according to its formulation, including the addition of 2% chitosan. Physical and chemical analyzes (pH, color, CRA, PPC, FC), microbiological analysis (counting at 350 and 450, Salmonella spp.) And centesimal composition were performed. As results, in the physical-chemical aspects there was no significant difference between the meat and the sausage, only in the HR in which the sausage had a lower shear force. As for the microbiological aspects, both the meat and the sausage presented within the parameters of the current legislation. In the centesimal composition both sausages had the above moisture content of the recommended one being this until 70% moisture content. As a conclusion, the formulation developed for the production of sausages, served the product aspects with low fat content, as well as obtaining values within the standard parameters established by the current legislation. Thus the formulation of this new product aims to seek strategies that make them healthy in relation to nutritional composition, with the insertion of a product in the market. In the second chapter, chitosan membranes containing propolis extract were developed in different concentrations. The chitosan was dissolved in 2% acetic acid under constant stirring using the magnetic stirrer for 24h. The propolis extract was activated and prepared in different concentrations. These solutions were placed in the oven for later drying. These membranes were characterized by the following analyzes: X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), differential thermal and thermogravimetric analysis (ATG / TG) and (DSC), scanning electron microscopy (SEM) and degree of swelling. In the development of the biomembranes it was possible to develop and stabilize the membranes with chitosan and propolis extract of the Frieseomelitta dorederleini bee at different concentrations. Demonstrating a new pharmaceutical form for application as a biological dressing in the pharmaceutical industry. The experimental data discussed in this study indicate that chitosan membranes with extracts of propolis from the Frieseomelitta dorederleini bee in different concentrations present features such as: poreless surface, higher content of mineral components, better thermal stability and good kinetics for water absorption. Favorable attributes for the application as curative membrane
Keywords: Biomaterial; embutidos cárneos; membrana; geoprópolis; melípona; biometerial; Meat sausages; membrane; geoprópolis; melípona; CIENCIAS AGRARIAS::ZOOTECNIA